(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2022)
Finger millet is staple food crop in drought-prone areas of the world and often considered as a component of food security strategies in Ethiopia. However, its yield is low in South Omo zone due to different production problems such as lack of improved varieties, lodging, and moisture stress in dry areas. A participatory finger millet variety selection was conducted at Kaysa, Baytesimal and Alga kebeles of Debube Ari District, South Omo Zone during the 2019-cropping season to identify high yielding finger millet variety/varieties .The field experiments was laid out in a randomized complete block design with three replications. The combined analysis’s of variance results revealed that there were significant (p<0.05) differences among varieties based on the recorded parameters except the harvest index. The maximum combined mean grain yield obtained to the varieties: Tadesse, Tesema and Kako-1 were 3746.75 kg ha-1, 3691.94 kg ha-1, and 3593.42 kg ha-1, respectively. While the minimum grain yield was recorded to variety, BKFM-0010 was 1341.18 kg ha-1. Regarding farmers’ preferences, variety Kako-1 and Tesema had higher grain yield followed by variety Tadesse. Based on data from researchers and farmers, varieties Tadesse, Tesema, and Kako-1 were the best varieties for the test agro-ecologies. Therefore; varieties; Tadesse, Tesema and Kako-1 could be recommended and popularized for use in the test areas and similar agro-ecologies. Int. J. Agril. Res. Innov. Tech. 12(1): 129-136, June 2022